Report on Development of Drought Prone Areas National Committee on the Development of Backward Areas - Planning Commission (Planning Commission, 1981)
Apart from the size and the geographical spread of the drought prone areas, another important consideration why it is necessary to formulate and implement an appropriate development strategy for these areas is that they represent a major factor contributing to regional imbalances in development of the country.
Planning Commission, Government of India